Analyses of Large Deflections of Simply Supported Nonlinear Beams, for Various Arc Length Functions - Eren, Ibrahim (SPRINGER HEIDELBERG, 2013)
In this paper, horizontal and largest vertical deflections have been calculated for uniformly distributed loaded, simply supported beams made of Ludwick type nonlinear material. Curvature expression for elastic curve had been defined according to two different arc length functions. Variations of horizontal and vertical deflections are tabulated depending on arc length functions, material, cross section and loading conditions.
Keywords: Large deflections; Geometrical nonlinearity; Material nonlinearity; Simply supported beams; Various arc length functions; NON-LINEAR MATERIALS; CANTILEVER BEAMS; Science & Technology - Other Topics